On a construction site – a change of perspectives. Architecture in Polish documentaries of the 1960s. - Otto, Wojciech (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Film documentaries: Energia [Energy] by Władysław Ślesicki and Czas przemiany [The Time of Transformation] by Andrzej Piekutowski are film examples of changing perspectives in Polish documentary film of the 1960s. The creators undertook the themes known from the socialist realism cinema, such as industrialization and the value of human labour, but they did so in the poetics of authorial cinema, creating films with a deeper, symbolic message and in a lyrical atmosphere.